HIGHLY CATALYTIC SCREEN-PRINTING INK - TIERNEY, Michael, J (2020)
The invention is directed to conductive polymer compositions, catalytic ink compositions (e.g., for use in screen-printing), electrodes produced by deposition of an ink composition, methods of making, and methods of using thereof. An exemplary ink material comprises platinum black and/or platinum-on-carbon as the catalyst, graphite as a conducting material, a polymer binding material, and an organic solvent. The polymer binding material is typically a copolymer of hydrophilic and hydrophobic monomers. The conductive polymer compositions of the present invention can be used, for example, to make electrochemical sensors. Such sensors can be used in a variety of analyte monitoring devices to monitor analyte amount or concentrations in subjects, for example, glucose monitoring devices to monitor glucose levels in subjects with diabetes.